The Comparison of Point Prevalence Survey (PPS) and Gyssens Flowchart Approach on Antimicrobial Use Surveillance in Indonesian National Referral Hospital - Erni J Nelwan; Helio Guterres; Adeline Intan Pasaribu; Sharifah Shakinah; Ralalicia Limato; Djoko Widodo (Interna Publishing, 2022)
The antimicrobial resistance (AMR) rate in Indonesia is steadily rising, despite the existing national action plan in 2014. In line with the Global Action Plan on AMR, proper surveillance on antimicrobial usage and resistance are needed. At present, antimicrobial surveillance (AMS) data in Indonesia is heterogeneous, fragmented, and localized. The common method of antimicrobial surveillance (AMS) in referral hospitals is by implementing Gyssens flowchart during Antimicrobial Resistance Control Program Committee clinical rounds. However, the recent method of AMS with Point Prevalence Survey (PPS) offers many advantages include its concise and simple protocol, large data collection, shorter required time, comprehensive data outcomes, real-time data, and standardized parameters. In low-middle income countries such as Indonesia with its restricted resources in AMS, PPS is superior compared to the 'traditional' hospital clinical round in generating representative and homogenous outcomes that can be compared to data from other centers worldwide.